Genetic evidence for involvement of vaccinia virus DNA-dependent ATPase I in intermediate and late gene expression. - Künzi, M S (1989)
To delineate the role of the vaccinia virus-encapsidated DNA-dependent ATPase I in the life cycle of the virus, we performed a detailed study of two temperature-sensitive mutants with lesions in the gene encoding the enzyme. Profiles of viral DNA and protein accumulation during infection showed the mutants to be competent for DNA synthesis but deficient in late protein synthesis, confirming their defective late phenotype (R. C. Condit and A. Motyczka, Virology 113:224-241, 1981: R. C. Condit, A. Motyczka, and G. Spizz, Virology 128:429-443, 1983). In vitro translation of viral RNA and S1 nuclease mapping of selected mRNAs demonstrated that the deficit in late protein synthesis stemmed from a defect in the transcriptional machinery. Intermediate and late gene expression appeared to be most affected. The transcriptional defect was of unequal severity in the two mutants. However, their phenotypes were indistinguishable and their respective lesions were mapped to the same 300 nucleotides at the 5' end of the gene. DNA sequence analysis assigned a single nucleotide and amino acid change to one of the mutants.